2021
DOI: 10.1016/j.heliyon.2021.e07418
|View full text |Cite
|
Sign up to set email alerts
|

Integrated multiplex network based approach for hub gene identification in oral cancer

Abstract: Background:The incidence of Oral Cancer (OC) is high in Asian countries, which goes undetected at its early stage. The study of genetics, especially genetic networks holds great promise in this endeavor. Hub genes in a genetic network are prominent in regulating the whole network structure of genes. Thus identification of such genes related to specific cancer types can help in reducing the gap in OC prognosis. Methods: Traditional study of network biology is unable to decipher the inter-dependencies within and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…One recent study identified 46 hub genes with 96% prediction accuracy, particularly PIK3CG, PIK3R5, MYH7, CDC20, and CCL4, which have significant biological implications for oral cancer and offered new research routes [21]. A study on head and neck squamous cell carcinoma patients identified 65 concordant genes, including a 13-gene panel.…”
Section: Discussionmentioning
confidence: 99%
“…One recent study identified 46 hub genes with 96% prediction accuracy, particularly PIK3CG, PIK3R5, MYH7, CDC20, and CCL4, which have significant biological implications for oral cancer and offered new research routes [21]. A study on head and neck squamous cell carcinoma patients identified 65 concordant genes, including a 13-gene panel.…”
Section: Discussionmentioning
confidence: 99%
“…Salivary biomarkers can be viewed from several perspectives, such as genomics, proteomics, metabolomics, and microbiomics (Fig. 2) Additionally, focus should be placed on comprehensive analysis of the integrative multi-omics module, where the multiplex network represents such systems effectively and encodes far more information than isolated networks [31,32].…”
Section: Liquid Biopsymentioning
confidence: 99%
“…Each edge set, referred to as a layer, can represent a distinct type of data (e.g., transcriptomics and proteomics) or clinical condition (e.g., disease/health and responder/non-responder to a drug). Various methods have been proposed for the analysis of multiplex networks, many of which detect those nodes whose set of neighbors ( neighborhood ) is highly consistent across layers ( Buphamalai et al, 2021 ; Mahapatra et al, 2021 ; Peng et al, 2021 ). With highly consistent neighborhoods across layers may be prioritized as the most interesting ones for downstream computational or biological analysis.…”
Section: Introductionmentioning
confidence: 99%